2018
DOI: 10.20885/jaai.vol22.iss2.art2
|View full text |Cite
|
Sign up to set email alerts
|

Financial characteristics, human development index, and performance: a study of local governments in Indonesia

Abstract: This study aims to examine whether the financial characteristics and human development index (HDI) are associated with the performance of local governments administration in Indonesia. The sample consists of 385 local governments classifying expenditures into operating and capital expenditures (Sample 1) and 53 local governments classified expenditures into direct and indirect expenditures (Sample 2). Regression result for Sample 1 indicate that special allocation funds (dana alokasi khusus, DAK) have a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This result support the expectation that HDI support the local governent performance. The result of this study also support the previous study who found the HDI level improve the local government performance [10], reduce the economic inequality [6], and provide sources for economic growth [1][2][3]. This result also in line with Al-Nasser and Al Hallaq [12] who found the negative relationship between poverty and human development index in Jordan.…”
Section: Results and Discussion (Title Case And Bold)supporting
confidence: 89%
See 1 more Smart Citation
“…This result support the expectation that HDI support the local governent performance. The result of this study also support the previous study who found the HDI level improve the local government performance [10], reduce the economic inequality [6], and provide sources for economic growth [1][2][3]. This result also in line with Al-Nasser and Al Hallaq [12] who found the negative relationship between poverty and human development index in Jordan.…”
Section: Results and Discussion (Title Case And Bold)supporting
confidence: 89%
“…The result of the previous study shows that HDI have positive effect on the local government performance. Further, Saputra, and Ardila [10] focus on the effect of local government financial characteristics and HDI to the level of local government performance. They found that both financial characteristics and HDI have significant effect on local government performance.…”
Section: Introductionmentioning
confidence: 99%
“…First, although references (Wang et al, 2021) show a threshold effect in poverty alleviation through investment in human capital in the health sector, no studies have specifically examined this threshold in other contexts or other geographic areas. Second, although (Saputra et al, 2018) found a positive relationship between the effectiveness of budgets and special allocation funds with the proportion of capital expenditure as well as a positive relationship between regional financial independence and the human development index in Indonesia, there has been no study that comprehensively analyzes other economic characteristics and how they interact with these variables.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The dependent variable of the study is public service quality while the independent variable is public attention. (Sutaryo et al, 2022;Sutopo et al, 2018) the relationship between variables by doing a correlation test. In order to evaluate the hypothesis, the primary analysis method employed is panel data regression analysis.…”
Section: Research Variablesmentioning
confidence: 99%
“…Ever since the 1998 reforms, the Indonesian government made significant amendments to the constitution to regulate equal distribution of power through decentralization policy (Diprose et al, 2019). A set of laws are issued to regulate local government that started from Vol 13, Issue 4, (2023) E-ISSN: 2225-8329 the first stage UU/22/1999 1 to prepare for the implementation of decentralization for two years, the second stage is regulated in UU/32/2004 2 and the third stage is UU/23/2014 3 (Rini & Damiati, 2017;Sutopo et al, 2018). The existence of these regulations were meant to strengthen local autonomy so that it can give local governments more authority to manage resources and meet the needs of local people (Holzhacker et al, 2016;Mubarok et al, 2022).…”
Section: Introductionmentioning
confidence: 99%